Management and Governance of Community Learning Activities Centers in Majalengka District - Indrayogi Indrayogi; Dadang Sudirno (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACT The purpose of this activity is to look at the condition of PKBM management and governance in Majalengka Regency. This study contains a survey on the management of community learning activity centers in Majalengka Regency. This analysis was conducted to determine the level of development and management of PKBM. The analysis carried out in the outline consists of two things. First, analyze the development of PKBM. Second, look at the management of PKBM. The method used is a survey; the sample is PKBM heads throughout Majalengka Regency, totaling 35 people, using interview and documentation technical instruments. The implementation of community service activities is from September 2022 to January 2023. Based on the analysis of studies from the survey results, overall the performance of the PKBM activity process is good but still needs to be improved so that the quality of community education increases. From a management perspective, it needs to be improved, especially in terms of infrastructure, teachers, and education personnel to support learning activities. It can be concluded that the development and management of PKBM in Majalengka Regency are in the good category.Keywords: Governance; Management; Learning Centers.Â Â Â